2011
DOI: 10.1121/1.3514503
|View full text |Cite
|
Sign up to set email alerts
|

Target detection and localization in shallow water: An experimental demonstration of the acoustic barrier problem at the laboratory scale

Abstract: This study demonstrates experimentally at the laboratory scale the detection and localization of a wavelength-sized target in a shallow ultrasonic waveguide between two source-receiver arrays at 3 MHz. In the framework of the acoustic barrier problem, at the 1/1000 scale, the waveguide represents a 1.1-km-long, 52-m-deep ocean acoustic channel in the kilohertz frequency range. The two coplanar arrays record in the time-domain the transfer matrix of the waveguide between each pair of source-receiver transducers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…(10) and (9), one derives the expression for both the amplitude and travel time SSK of each eigenray path. As shown by Marandet et al, 13 the DBF-SSK for the normalized amplitude is numerically computed for any r 0 between the source and the receiver arrays as…”
Section: A Double Beamforming Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) and (9), one derives the expression for both the amplitude and travel time SSK of each eigenray path. As shown by Marandet et al, 13 the DBF-SSK for the normalized amplitude is numerically computed for any r 0 between the source and the receiver arrays as…”
Section: A Double Beamforming Transformationmentioning
confidence: 99%
“…For example, in underwater acoustics, travel time tomography has been recently developed with the sensitivity kernel 12 to predict the arrival-time change of the acoustic echoes. Similarly, a recent paper has experimentally shown that the sensitivity kernel for a local change in density 13 or sound speed 14 could be used for the localization of a target or a temperature anomaly in an ultrasonic waveguide. Both results apply to multipath propagation media (shallow or deep water ocean) in which the acoustic field is perturbed by a local volume change.…”
Section: Introductionmentioning
confidence: 97%
“…sensitivity kernel analysis. 22,23 But here the variation in the functional error is given in energy instead of amplitude.…”
Section: B Signal Processingmentioning
confidence: 99%
“…As such, the optimal subarray size results from a balance between resolution and robustness. [22][23][24] Large subarrays provide enhanced angular resolution. However, when there are strong heterogeneities close to the transducer arrays, as is often the case for geomaterials (where localized deformations may spread across the entire sample), beamforming performs better with shorter subarrays.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%